What can countries learn from Hong Kong’s response to the COVID-19 pandemic? - Wong, Samuel Y.S.; Kwok, Kin On; Chan, Francis K.L. (Canadian Medical Association journal (CMAJ), 2020)
The first case of COVID-19 in Hong Kong was reported on Jan 22, 2020. From January to Mar 2020, 96,709 tests were performed, and by Apr 14, 2020, 1010 people had tested positive for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and 4 had died from COVID-19. Given its unique circumstances, Hong Kong has done relatively well in controlling the spread of COVID-19. Here, Wong et al analyze the potential reasons for Hong Kong's early success in preparing for and reacting to the SARS-CoV-2 threat.